Capillary condensation-driven growth of perovskite nanowire arrays for multi-functional photodetector - Gangjian Hu; Jiajun Guo; Jizhong Jiang; Lei Wang; Jiaqi Zhang; Hongxu Chen; Gangning Lou; Wei Wei; Liang Shen (Light: Science & Applications)
Abstract Metal-halide perovskite nanowire array photodetectors based on the solution method are valuable in the field of polarized light detection because of their unique one-dimensional array structure and excellent photoelectric performance. However, the limited wettability of liquids poses challenges for achieving large-scale and high-quality perovskite nanowire arrays. To address this issue, we develop a facile method utilizing capillary condensation to grow high-quality centimeter-scale perovskite nanowire arrays. Based on these nanowires, the fabricated photodetector showcases specific detectivities of 1.95 × 1013 jones, surpassing commercially available silicon detectors in weak-light detection capabilities. The weak-light imaging capability of our nanowire photodetectors has been successfully demonstrated at intensities below 54 nW/cm2. Moreover, the nanowire arrays also display excellent polarization absorption characteristics, promising applications in polarized light detection. Notably, the perovskite nanowire arrays can be grown on flexible substrates by employing capillary condensation, which retains 83% of their properties after 2000 bending cycles. This research enhances the potential of perovskite nanowire arrays photodetector in practical applications.